Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How to find limit of this?

\begin{equation} \lim_{h \rightarrow 0} \frac {\sqrt[3]{x+h} - \sqrt[3]{x}} {h}. \end{equation}

I see here the derivative definition, so I understand in "derivative mind" that answer has to be \begin{equation} \frac{1}{3} x^{-\frac{2}{3}}, \end{equation}but in the book this expression goes before derivatives, so it must be another approach to find this limit.

share|cite|improve this question
Rationalize the numerator. – David H Jul 26 '14 at 11:08
up vote 5 down vote accepted

Hint: $$(a-b)(a^2+ab+b^2)=a^3-b^3.$$

share|cite|improve this answer

Rationalise the numerator by the identity $a^3-b^3=(a-b)(a^2+ab+b^2)$

$\lim _{h\rightarrow 0}{\frac {\sqrt [3]{x+h}-\sqrt [3]{x}}{h}}$

$=\lim _{h\rightarrow 0}{\frac {\sqrt [3]{x+h}-\sqrt [3]{x}}{h}}{\frac { \left( x+h \right) ^{2/3}+\sqrt [3]{x+h}\sqrt [3]{x}+{x}^{2/3 }}{ \left( x+h \right) ^{2/3}+\sqrt [3]{x+h}\sqrt [3]{x}+{x}^{2/3}}} $

$=\lim _{h\rightarrow 0}{\frac {(x+h)-x}{h \left( \left( x+h \right) ^{2/3}+ \sqrt [3]{x+h}\sqrt [3]{x}+{x}^{2/3} \right) }}$

$=\lim _{h\rightarrow 0}{\frac {1}{ \left( x+h \right) ^{2/3}+ \sqrt [3]{x+h}\sqrt [3]{x}+{x}^{2/3} }}$

$={\frac {1}{ \left( x \right) ^{2/3}+ \sqrt [3]{x}\sqrt [3]{x}+{x}^{2/3} }}$ by plugging in $h=0$



share|cite|improve this answer


Another one (assuming $x\neq 0$) :$$\sqrt[3]{x+h}=x^{\frac{1}{3}}\sqrt[3]{1+\frac{h}{x}}$$ Now, if you remember that, when $y$ is small, $(1+y)^a \simeq 1+ ay$, then now, replace $y$ by $\frac{h}{x}$ and so $$ \sqrt[3]{x+h}=x^{\frac{1}{3}}\sqrt[3]{1+\frac{h}{x}}\simeq x^{\frac{1}{3}}(1+\frac{h}{3x})=x^{\frac{1}{3}}+\frac{h}{3x^{\frac{2}{3}}}$$

I am sure that you can take from here.

share|cite|improve this answer
Very useful for me. – Leo Matyushkin Jul 26 '14 at 11:29
You are very welcome. Remember this approximation : you will use it a lot in your studies. Cheers :) – Claude Leibovici Jul 26 '14 at 11:31


Set $\displaystyle\sqrt[3]{x+h}=a\implies x+h=a^3,\sqrt[3]x=b\implies x=b^3; a^3-b^3=h$

As $\displaystyle h\to0, a\to b\implies a\ne b$

Finally, the limit should be $\displaystyle3/b^2=3/(x^{\dfrac23})$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.